Addition of Hyperbaric Oxygen Therapy vs Medical Therapy Alone for Idiopathic Sudden Sensorineural Hearing Loss: A Systematic Review and Meta-analysis - Rhee, Tae-Min (JAMA Otolaryngol Head Neck Surg, 2018)
IMPORTANCE: Sudden sensorineural hearing loss (SSNHL) causes substantial disease burden for both individuals and socioeconomic aspects. The benefit of hyperbaric oxygen therapy (HBOT) in addition to standard medical therapy (MT) for idiopathic SSNHL has been unclear. OBJECTIVE: To perform a systematic review and meta-analysis to compare HBOT + MT with MT alone as a treatment for patients with SSNHL. DATA SOURCES: PubMed, Embase, and the Cochrane Database of Systematic Reviews were systematically searched up to February 2018. STUDY SELECTION: Randomized clinical trials and nonrandomized studies comparing HBOT + MT with MT alone for SSNHL treatment. DATA EXTRACTION AND SYNTHESIS: Two investigators independently screened the eligible studies, established data, and assessed quality and risk of bias. A systematic review and meta-analysis using random-effects models was conducted. MAIN OUTCOMES AND MEASURES: The primary outcome was complete hearing recovery, and secondary outcomes were any hearing recovery and absolute hearing gain. RESULTS: Three randomized clinical trials and 16 nonrandomized studies comparing outcomes after HBOT + MT vs MT alone in 2401 patients with SSNHL (mean age, 45.4 years; 55.3% female) were included. Pooled odds ratios (ORs) for complete hearing recovery and any hearing recovery were significantly higher in the HBOT + MT group than in the MT alone group (complete hearing recovery OR, 1.61; 95% CI, 1.05-2.44 and any hearing recovery OR, 1.43; 95% CI, 1.20-1.67). Absolute hearing gain was also significantly greater in the HBOT + MT group than in the MT alone group. The benefit of HBOT was greater in groups with severe to profound hearing loss at baseline, HBOT as a salvage treatment, and a total HBOT duration of at least 1200 minutes. CONCLUSIONS AND RELEVANCE: The addition of HBOT to standard MT is a reasonable treatment option for SSNHL, particularly for those patients with severe to profound hearing loss at baseline and those who undergo HBOT as a salvage treatment with a prolonged duration. Optimal criteria for patient selection and a standardized regimen for HBOT should be applied in routine practice, with future trials to investigate maximal treatment benefit.